Schaum's Statistics Supplementary Problem 6.59 : Mathematical Expectation of Discrete Random Variable - Rader, David (McGraw-Hill's AccessEngineering, 2020)
This video demonstrates how to compute the expected value of a discrete random variable as well as the computation of the expected value of various functions of the random variable.